Teaching in a Digital Age Guidelines for designing teaching and learning - Bates, A.W. (Tony) (Open textbook library., 2019)
Teachers, instructors and faculty are facing unprecedented change, with often larger classes, more diverse students, demands from government and employers who want more accountability and the development of graduates who are workforce ready, and above all, we are all having to cope with ever changing technology. To handle change of this nature, teachers and instructors need a base of theory and knowledge that will provide a solid foundation for their teaching, no matter what changes or pressures they face. Although the book contains many practical examples, it is more than a cookbook on how to teach. It addresses the following questions: is the nature of knowledge changing, and how do different views on the nature of knowledge result in different approaches to teaching? what is the science and research that can best help me in my teaching? how do I decide whether my courses should be face-to-face, blended or fully online? what strategies work best when teaching in a technology-rich environment? what methods of teaching are most effective for blended and online classes? how do I make choices among all the available media, whether text, audio, video, computer, or social media, in order to benefit my students and my subject? how do I maintain high quality in my teaching in a rapidly changing learning environment while managing my workload? what are the real possibilities for teaching and learning using MOOCs, OERS, open textbooks? In summary, the book examines the underlying principles that guide effective teaching in an age when everyone, and in particular the students we are teaching, are using technology. A framework and a set of guidelines are suggested for making decisions about your teaching, while understanding that every subject is different, and every teacher and instructor has something unique and special to bring to their teaching. In the end, though, the book isn't really about teachers and instructors, although you are the target group. It's about you helping your students to develop the knowledge and skills they will need in a digital age: not so much digital skills, but the thinking and knowledge that will bring them success. For that to happen, though, your students need you to be on top of your game. This book is your coach.